Peran Ayah dalam Pengasuhan Anak (Studi Kasus Pemenang Keluarga Sakinah Tingkat Nasional Tahun 2016) - Ratih Nur Aini (FAI, 2017)
Peran Ayah dalam Pengasuhan Anak (Studi Kasus Pemenang Keluarga Sakinah Tingkat Nasional Tahun 2016)